2010
DOI: 10.4236/me.2010.13015
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Egyptian Agricultural Exports: A Gravity Model Approach

Abstract: In this paper, a gravity model approach was employed to analyze the main factors influencing Egypt’s agricultural exports to its major trading partners for the period 1994 to 2008. Our findings are that a one percent increase in Egypt’s GDP results in roughly a 5.42 percent increase in Egypt’s agricultural export flows. In contrast, the increase in Egypt’s GDP per capita causes exports to decrease, which is attributed to the fact that an increase in economic growth, besides the increasing population, raises th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 12 publications
6
48
1
6
Order By: Relevance
“…In the case of Albania not all RTAs and FTAs have the same effect on agricultural trade, in our study export creating affect was confirmed for RTA with CEFTA 2006 countries and export diversion effect for FTA with EFTA countries. According to gravity model for Egypt's agricultural exports (Hatab et al, 2010) 1% increase in Egypt's GDP generates more than 5% increase in its agricultural export flows. In contrast, the increase in Egypt's GDP per capita causes exports to decrease, similarly as in our model.…”
Section: Discussion and Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Albania not all RTAs and FTAs have the same effect on agricultural trade, in our study export creating affect was confirmed for RTA with CEFTA 2006 countries and export diversion effect for FTA with EFTA countries. According to gravity model for Egypt's agricultural exports (Hatab et al, 2010) 1% increase in Egypt's GDP generates more than 5% increase in its agricultural export flows. In contrast, the increase in Egypt's GDP per capita causes exports to decrease, similarly as in our model.…”
Section: Discussion and Remarksmentioning
confidence: 99%
“…Hence, Albanian migrants might lower information and transaction costs through knowledge of homecountry markets, language, business contracts etc. Therefore, empirical studies suggest that larger migrant stocks are associated with higher trade flows (see Gould, 1994 Effects of exchange rate are frequently incorporated in gravity models dealing with agricultural trade (see Koo et al, 1994;Frankel and Wei, 1998;Hatab et al, 2010). In our case, annual exchange rate is determined by the Albania's currency units (ALL/Albanian Lek) per one unit of the importing country currency.…”
Section: Model Variablesmentioning
confidence: 98%
“…Os modelos de gravidade aumentados ou estendidos (ver OGULEDO e MACPHEE, 1994) têm sido utilizados para análise de comércio desagregado, tendo obtido resultados bastante robustos. Por exemplo, Hatab et al (2010) aplicaram o modelo de gravidade para analisar os principais fatores que influenciam as exportações agrícolas do Egito para seus principais parceiros comerciais (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008). O trabalho mostrou que um aumento de 1% nas respectivas rendas brutas do Egito e de seus parceiros comerciais provocaria uma elevação de 0,74% e 5,73% no comércio bilateral de produtos agrícolas daquele país.…”
Section: Modelo De Gravidade Deunclassified
“…Following Hatab, Romstad, and Huo () and Sheldon, Khadka Mishra, Pick, and Thompson (), importer fixed effects were applied to control for country‐specific influences on trade flows. The distance variable was thus dropped as it would have been collinear with the importer fixed effects.…”
Section: Methods and Datamentioning
confidence: 99%